Dietary inclusion of methanotrophic microbial cell-derived protein in the early postweaning period sustains growth performance and intestinal health of weaner piglets - Mette Skou Hedemann; Marie Rønn; Marleen Elise van der Heide; Ina Karlshøj Julegaard; Mette Olaf Nielsen (Animal, 2023)
The global demand for sustainably produced protein feeds for animal production is increasing. Methanotrophic bacteria grow on methane and convert it into microbial cell protein (MCP) that has been shown to have high nutritive value for growing pigs. The present aimed to investigate how increasing amounts of MCP in diets fed during the first 15 days after weaning affect the growth performance of piglets from weaning until day 43 postweaning. Furthermore, the effect of MCP on intestinal morphology and histopathology was assessed on day 15 after weaning. During seven consecutive weeks, approximately 480 piglets were recruited for the experiment per batch. The piglets were divided into four groups and housed in eight double pens with 60 piglets per pen. The piglets were fed one of four experimental diets with 0, 3, 6, or 10% of MCP included at the expense of fishmeal and subsequently potato protein for the first 15 days postweaning. Thereafter, all pigs were fed commercial weaner diets in two phases (days 16–30 and days 31–43) until day 43 postweaning. All diets were without medicinal zinc. Feed intake and growth were registered on double pen level during all three phases. On day 15 after weaning, 10 piglets per treatment were randomly selected, autopsied, and sampled for intestinal morphology and histopathology. Daily gain during the first 15 days postweaning tended (P = 0.09) to be affected by the inclusion of MCP in the weaning diet being lowest in the group fed 10% MCP. Treatment did not affect daily feed intake; however, Feed Conversion Ratio (FCR) was significantly affected (P = 0.003) showing the highest FCR in piglets fed 10% MCP. Growth performance was not affected by the experimental treatment during the following phases. In the small intestine, villous height tended (P = 0.09) to show a quadratic response to level of MCP in the diet with the longest villi observed after feeding 6% MCP. Dietary treatment did not affect crypt depth. The villous height to crypt depth (VC) ratio showed a quadratic response to increased dietary inclusion of MCP (P = 0.02) with piglets fed 6% MCP having the highest VC ratio. In conclusion, this study demonstrated that MCP could constitute 6% of diets as-fed (22% of total CP), at the expense of fishmeal and potato protein, for newly weaned piglets without negative effects on growth rates and FCR. The inclusion of MCP in diets for newly weaned piglets could be part of improving the sustainability of pig production.